FORMULASI DAN UJI ANTIBAKTERI SABUN MANDI PADAT EKSTRAK ETANOL DAUN JAMBLANG (Syzygium cumini (L) Skeels) TERHADAP Staphylococcus aureus - Himyatul Hidayah; Eko Sri Wahyuningsih; Surya Amal; Ananda Kamila (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Staphylococcus aureus bacteria is one of the microorganisms that cause infectious diseases of the skin. Jamblang leaves (Syzygium cumini (L) Skeels) contain bioactive compounds with antibacterial potential such as alkoloids, flavonoids, saponins, steroids, and tannins. The purpose of this study was to analyze the antibacterial activity of extracts and solid soap preparations from ethanol extracts of jamblang leaves that have potential as antibacterial Staphylococcus aureus. Method: jamblang leaf simplisia powder was macerated with 70% ethanol solvent, thick extract of jamblang leaf was tested for antibacterial activity inhibition using disc diffusion method. Solid soap preparations were made with three concentrations of jamblang leaf extract addition, namely F1 (5%), F2 (6.25%) and F3 (7.5%). The results showed that the solid soap of 70% ethanol extract of jamblang leaves can inhibit Staphylococcus aureus bacteria at all three concentrations. Formulation 1 (5%) solid soap has an inhibition zone of 6.93mm ± 0.85, Formulation 2 (6.25%) 8.61mm ± 0.99 and Formulation 3 (7.5%) 11.2mm ± 1.90. This study can be concluded that the three formulations can inhibit Staphylococcus aureus bacteria.